A CONCEPTUAL MODEL ANALYSIS OF SST INFLUENCE ON MARINE BIOTA IN THE SOUTH JAVA SEA - Albert Sulaiman; Nani Hendiarti (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2012)
We developed a conceptual coupled atmosphere-ocean-ecosystem model for the South Java seas to investigate interaction between marine biota and SST variability due to monsoon-forced. Ocean and atmosphere are represented by a box model for one dimensional water column. The equation of motions of the zonal wind stress and SST are represented in term of nonlinear oscillator model. Marine biota are represented by three components (nutrient, phytoplankton and zooplankton) of NPZ Edward-Brindley model. The marine ocean-atmosphere coupling mechanism is done through the absorption of blue light by phytoplankton. The system of nonlinear dynamical equation is solved by using Matlab ODE solvers. Monthly SST data is used to compare the model. Result showed that the period and amplitude of oscillation of SST and ecosystem component strongly depend on the parameter choice which describes the dynamical characteristic of the system. The SST and ecosystem variability will strongly correlate with monsoonal wind if we choose the parameter of light attenuation by water 0.2 m-1. Strong seasonal variations associated with monsoonal winds were observed for SST, phytoplankton and zooplankton concentration. On the other hand, the nutrient concentration shows a weak seasonal variationKeywords: SST, NPZ, monsoon, delayed oscillator